2014
DOI: 10.5539/sar.v3n2p24
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Cabbage (Brassica oleraceae Var capitata) Yields and Quality Through Microclimate Modification and Physiological Improvement Using Agronet Covers

Abstract: Adverse environmental conditions have contributed to perpetual poor cabbage (Brassica oleraceae var. capitata) yields in sub-Saharan Africa. Elsewhere, net covers have been reported to provide a low-cost technology with the potential of modifying the microclimate around a crop for better performance. Two experiments were therefore conducted over a span of two seasons to determine the effects of agronet covers on microclimate modification and subsequent cabbage yield and quality. The treatments comprised cabbag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
5
12
0
Order By: Relevance
“…Besides reduced transpiration rates, existence of a net cover may also have reduced soil evaporation rate under netted areas due to restricted air movement, resulting in higher soil water retention. Findings of the current study corroborate those of earlier studies on spinach (Meena et al, 2014), and cabbage under net covers (Muleke et al, 2014). Among the agro-net covers, soil moisture tended to be higher under coloured-colour net covers than under neutral-colour net covers possibly due to the higher relative humidity levels and lower air temperature recorded under coloured-colour net covers than under neutral-colour net covers that may have contributed to reduced evapotranspiration rate and higher soil moisture levels.…”
Section: Journal Of Agricultural Sciencesupporting
confidence: 83%
“…Besides reduced transpiration rates, existence of a net cover may also have reduced soil evaporation rate under netted areas due to restricted air movement, resulting in higher soil water retention. Findings of the current study corroborate those of earlier studies on spinach (Meena et al, 2014), and cabbage under net covers (Muleke et al, 2014). Among the agro-net covers, soil moisture tended to be higher under coloured-colour net covers than under neutral-colour net covers possibly due to the higher relative humidity levels and lower air temperature recorded under coloured-colour net covers than under neutral-colour net covers that may have contributed to reduced evapotranspiration rate and higher soil moisture levels.…”
Section: Journal Of Agricultural Sciencesupporting
confidence: 83%
“…From the current study, higher yields in terms of fruit number and weight was obtained with the use of agronet cover and companion planting with a 35%-51% increase in fruit number under agronet cover alone while combined use of agronet cover and companion planting with a row of basil in between adjacent rows of tomato recorded 72%-86.1% increase in tomato fruit number and 80%-83.5% increase in tomato fruit weight compared with the control. Results of the current study corroborate findings by [45,46] who reported increase in marketable yield by up to 70% in tomato and 58% in cabbage, respectively, and a reduction in non-marketable yield by up to 60% following the use of agronet covers compared to control treatments. Besides the shading effect offered by agronet covers and companion planting, net covers have been documented to modify air temperature and the diurnal temperature range hence providing ideal growth condition resulting to improved yield.…”
Section: Discussionsupporting
confidence: 90%
“…Insect proof nets are believed to be a suitable solution to reduce the use of insecticides and to protect vegetable crops from the emergence of new devastating insect pests for which chemical treatments are not effective (Martin et al 2014b). Several studies on cabbage (Brassica oleracea L.) in Benin (Martin et al 2006;Licciardi et al 2007) and later in Kenya (Kiptoo et al 2015;Muleke et al 2012Muleke et al , 2014, on tomato (Lycopersicon esculentum Mill.) (Gogo et al 2014a;Saidi et al 2013;Gogo et al 2012), and on green beans (Phaseolus vulgaris L.) in Kenya (Gogo et al 2014b) have reported the advantage of using insect proof nets to exclude insect pests.…”
Section: Control Of Insect Pests With Protected Cultivationmentioning
confidence: 99%